Wall motion tracking in fetal echocardiography—Application of low and high frame rates for strain analysis. - Enzensberger, Christian; Rostock, Laura; Graupner, Oliver; Götte, Malena; Wolter, Aline; Vorisek, Carina; Herrmann, Johannes; Axt‐Fliedner, Roland (Echocardiography, 2019)
Objective: Compared to adults, fetal heart rates (HR) are elevated necessitating higher frame rates (FR) for strain analysis by speckle tracking echocardiography. The aim of this study was to investigate the influence of high FR compared to low FR on strain analysis in 2D speckle tracking. Methods: Fetal echocardiography was prospectively performed and acquired from the apical or basal four‐chamber views of the heart. Images were optimized for clear delineation of myocardial walls and stored in either raw Digital Imaging and Communications in Medicine (DICOM) cine‐loop format for offline analysis with a low FR of 60 frames per second (fps) or in the original FR (acoustic FR = AFR). For each loop, right (RV) and left (LV) ventricular fetal longitudinal peak systolic strain (LPSS) values were assessed by 2D Wall Motion tracking. Results: One hundred and three healthy fetuses were included with a mean gestational age of 26.3 ± 5.5 weeks. Mean AFR was 127 ± 26 fps. A mean FR/HR ratio was assessed of 0.42 and 0.90 between the low FR and AFR group, respectively. Relating to LPSS values, there was a significant difference between low FR and AFR for both ventricles (LV: −16.5% ± 3.9% (low FR) vs −13.6% ± 3.5% (AFR); and RV: −15.1% ± 3.6% (low FR) vs −12.6% ± 3.7% (AFR), both P < 0.001). Conclusions: Fetal LV and RV LPSS values derived with high AFR were significantly lower than corresponding LPSS values analyzed with low FR of 60 fps. Future studies are needed to clarify the clinical importance of this relationship.